Effect of cardiac rehabilitation on cognitive function in elderly patients with cardiovascular diseases - Fujiyoshi, Kazuhiro (PLoS One, 2020)
BACKGROUND: Cognitive function is an important factor for secondary prevention in elderly patients with cardiovascular diseases. The objective of this study was to evaluate the impact of cardiac rehabilitation (CR) on the improvement of cognitive function. METHODS: A total of 66 consecutive elderly patients (≥70 years old) with cardiovascular diseases were prospectively enrolled. The change in cognitive function during 6 months was compared between the patients with monthly CR (at least once per month; n = 27) and those without monthly CR (n = 39). Cognitive function was evaluated using the Mini-mental State Examination (MMSE) and Frontal Assessment Battery (FAB). RESULTS: There was no significant difference in baseline characteristics between the 2 groups. The change in the MMSE score was significantly greater in patients with monthly CR than in those without monthly CR (2.3 ± 0.4 vs. −0.1 ± 0.3 points; p <0.001). Among the MMSE items, the change in temporal orientation and attention and calculation was significantly greater in the monthly CR group than in the non-monthly CR group (0.8 ± 0.7 vs. −0.1 ± 0.8 points [p <0.001] and 1.0 ± 1.5 vs. −0.1 ± 0.1 points [p <0.001], respectively). The general linear model revealed that monthly CR (effect estimate, 1.455; 95% confidence interval, 0.747–2.163; p <0.001) was independently associated with the change in the MMSE score. CONCLUSIONS: Cognitive function may improve with regular CR. These results might partly explain the efficacy of CR for secondary prevention.